IMPLEMENTASI ALOKASI DANA DI DEA ILUGAWA DISTRIK ILUGAWA KABUPATEN MAMBERAMO TENGAH PROPINSI PAPUA - Andi - Walela (JI@P, 2014)
Village budget allocation is the manifestation of the village right. Such kind ofbudget is intended to grow and to develop the village based on communitydiversity, participation, indigenous otonomy, democratization, and empowerment.In such, baudget allocation is able to increase role of Local Government in servingand increasing community welfare. It is expected that left-behind areas can bedeveloped integrating into the area system developmet. Achieving suchobjectives, however, the implementation of budget allocation faces someobstructions. This study is intended to comprehend problems related to the villagebudget allocation. Research was conducted in Ilugawa Village, Ilugawa District,Mambramo Tengah Regency, Papua Province. Qualitative research method wasused in this study. Interview and documentation study were used as datacollecting method. Componential analysis technique was employed to analysisthe elements that are considered to have relational contradictory domains.Research result shows that the budget is implemented according to the existingprocedure, however, there is problem in writing report the budget responsibility. Itis needed to be assisted by the District Government level. Research result alsoshows that human resources, attitude of implementer, bureaucratic structure,bureaucratic environment, and standard as well as objective of policy impinge theimplementation of budget allocation. Other factors influencing budget allocationare village head domination in appointing the team members and thetransportation of construction materials.Key words: Village budget allocation, componential analysis technique, humanresources, attitude of implementer, bureaucratic structure, bureaucraticenvironment, standard of policy.